(untitled) (Tanzania Medical Journal, 2007)
Background: Chlorine-based antiseptics and disinfectants have a stability problem especially when formulated as aqueous solutions. They tend to decompose slowly liberating chlorine on storage. Despite this instability, these products are commonly manufactured and labeled with a long shelf-life. Thus the labeled content of available chlorine is doubtful and this could pose a danger to public health by not providing adequate disinfection. Broad Objective: This study aimed at assessing the quality of chlorine-based antiseptics and disinfectants circulating in Dar es Salaam, Tanzania. Study setting: The study was carried out in the city of Dar es Salaam Methods and materials: Nineteen (19) samples representing various product batches circulating in Dar es Salaam were collected randomly from pharmacies, shops and from a tertiary-level public hospital. Analysis of the samples was immediately done in which the content of available chlorine was determined using a titrimetric method (Iodometric titration) according to the British Pharmacopoea (BP) specifications. Measures of outcome: Results for contents of available chlorine was compared to the limits of assay specified in the BP and thus the percent compliance was calculated. Samples with contents below that specified in the BP were deemed to have failed the quality tests. For those products for which no official specifications are available (eg. Waterguard®), the BP limits for assay (± 10% of label claim) was applied to assess compliance. Results: Out of the 19 sample batches analyzed 12 (63%) did not comply with the specifications for available chlorine (BP Limits of Assay or within 90-110% manufacturer's label claim). This was especially serious with preparations containing calcium hypochlorite with boric acid (Eusol) which had a mean content of only 12% of the recommended strength. Conclusion and recommendations: The results from this study have shown clearly that chlorine-based antiseptics/disinfectant products should not be manufactured on a large scale by pre-dilution. Rather, they should be supplied as concentrates or powders for reconstitution at the time of use to ensure quality, efficacy and safety to public health. Tanzania Medical Journal Vol. 22 (1) 2007: pp. 17-19